Antibiotic Susceptibility and Biofilm Production among Coagulase Negative Staphylococci Isolated from Clinical Samples at Tertiary Care Hospital - Shah, Pradeep Kumar; Bhandari, Niru; Tamang, Basanta; Joshi, Rajendra D (Journal of Nepal Health Research Council, 2024)
Background: Coagulase Negative Staphylococci have been widely associated with medical device implant treatment and immune-compromised patients. Despite having increasing interest in Coagulase Negative Staphylococci, few studies from Nepal have reported the association of these organisms with urinary tract infections, conjunctivitis, high vaginal swabs, and cerebrospinal fluid. This study was carried out to determine antibiotic susceptibility pattern and biofilm production among Coagulase Negative Staphylococci isolated from clinical samples at tertiary care hospital.Methods: This study was a hospital based cross-sectional study in which 3690 clinical samples were included. Isolation and identification of isolates was done following standard microbiological protocol. Coagulase Negative Staphylococci were identified phenotypically on the basis of gram staining, slide and tube coagulase test and by various sugar fermentation tests. Antibiotic susceptibility test was done following Kirby Bauer disk diffusion method (Clinical and Laboratory Standards Institute 2020). Biofilm production was determined by Tissue Culture Plate technique. Results: A total of 113 isolates of Coagulase Negative Staphylococci were detected. Among them S. epidermidis (45.1%), S. saprophyticus (23.9%), S. haemolyticus (16.8%), S. hominis (5.3%), S. capitis (2.7%), S. cohini (1.8%), S. lugdunensis (1.8%) and S. sciuri (2.7%) were identified phenotypically. All isolates were found to be resistant against Ampicillin and 111 (98.2%) were sensitive against Linezolid.23.9% of CoNS were strong biofilm producers, 19.5% moderate and 56.6 % were non/weak biofilm producers.Conclusions: It requires susceptibility test for prescribing antibiotics against Coagulase Negative Staphylococci in hospital and the misuse of antibiotics should be prevented.Keywords: Clinical samples, CoNS, antibiotic susceptibility, biofilm